Analysis of Teaching Style of High Grade Teachers in Narrative Writing Learning in Wado District - Budianty, Noviana; Sunendar, Dadang (International Conference on Elementary Education, 2022)
This study aims to analyze and determine the teaching styles used by upper class teachers in Wado District, Sumedang Regency in learning to write narratives. Respondents in this study were teachers in 13 schools in the sub-district. The research approach used is a qualitative approach through descriptive methods with the type of survey research. Data retrieval was done by distributing questionnaires through google form which then data were analyzed by means of data reduction, data presentation, and drawing conclusions. There are seven indicators that are used as a reference to see the sequence of learning carried out by the teacher. Meanwhile, to analyze the teacher's teaching style, it was translated into 15 questions from all indicators of the teacher's teaching style. After collecting data, it was concluded that the dominant teaching style used by teachers in learning to write narratives was interactional teaching style as much as 77.40%. At the implementation stage of learning to write narratives, not all teachers apply these indicators. The percentage of the application of narrative writing indicators that is mostly done by teachers is indicator 1, which is guiding students in determining the theme, topic, and mandate to be delivered. The percentage is 84.6%. Meanwhile, the lowest indicator is indicator 3, which is setting a target readership with a percentage of only around 30.7%.